IMPLEMENTASI PERATURAN BUPATI KUTAI KARTANEGARA NOMOR 46 TAHUN 2011 TENTANG PELAYANAN REHABILITASI RUMAH TIDAK LAYAK HUNI DI KABUPATEN KUTAI KARTANEGARA - Mudji Sulistiyo (Jurnal Paradigma (JP), 2017)
The implementation of Head District’s Role Number 46 Year 2011 about the home rehabilitation service in Kutai Kartanegara. It is a kind of public service that can influence the quality life of the society. Influence factors in implementing this program are service procedure, finalization time, service cost.